Cardiovascular Risk and Quality of Life in Elderly People with Mild Thyroid Hormone Deficiency - Tognini, Sara; Pasqualetti, Giuseppe; Calsolaro, Valeria; Polini, Antonio; Caraccio, Nadia; Monzani, Fabio (Frontiers in Endocrinology, 2014)
Subclinical hypothyroidism (sHT) is a common condition in the general population, the prevalence increasing with ageing, especially in women. An association between sHT and increased coronary heart disease (CHD) and heart failure (HF) risk and mortality has been described. However, this association is far to be established in older people (>65 years), especially in the oldest old (>85 years). Individuals with sHT may experience symptoms that resemble those observed in the overt form of the disease, leading to an impaired quality of life (QoL). Although very old people are frequently frail and potentially more susceptible to the effects of a disease, few studies were designed to assess the effect of sHT on QoL in this subset of population. Interestingly, the serum TSH concentration curve of general population has a skewed distribution with a “tail” toward higher values, which is amplified with ageing. Thus, the diagnosis of sHT and the interpretation of its potential effects on CV function and QoL in older people may be a challenge for the clinician. Giving these premises, we reviewed the English scientific literature available on National Library of Medicine (www.pubmed.com) since 1980 regarding: hypothyroidism, subclinical hypothyroidism, elderly, cardiovascular risk, coronary heart disease (CHD) or heart failure (HF) events and mortality, health-related QoL, LT4 therapy. Consistent results among large prospective cohort studies suggest an age-independent relationship between sHT and HF progression while, an impact of sHT on CHD events and mortality is essentially reported in young adults (aged below 65-70 years) with long-lasting disease. Scanty data are available on QoL of older people with sHT (>65 years) and, generally, no significant alterations are described.